Political Science in Latin America: A Scientometric Analysis - Codato,Adriano (2020)
Studies of Latin American political science are centered on analyses of national cases and are based on intellectual narratives about the institutional development and teaching of the discipline. In this article we take a different, more comprehensive and comparative approach. We distinguish and contrast two Latin American political sciences: one native to Latin America and published in journals from five countries in the region, and one foreign and published in journals from five countries outside the region. We use three types of bibliometric measures: 01. reciprocal citations in 23 academic journals indexed in the Scopus database; 02. co-occurrence of terms in titles and abstracts of 5,880 research articles published between 2006 and 2018; and 03. co-citations of authors in the bibliographies of said articles. The network of journals forms a well-defined archipelago with three clusters separated by language (English, Spanish and Portuguese). The community is divided along two main axes: political approaches versus sociological approaches. The study also points out that themes, authors, and methodologies are not significantly different between these two political sciences.